Hubungan Pengetahuan, Religiusitas, dan Lingkungan Sosial Terhadap Minat Menabung Menggunakan Bank Syariah - Khairunnisa, Isma Aulia; Cahyono, Hendry (Jurnal Ekonomika dan Bisnis Islam, 2020)
Islamic banks still have obstacles, one of which is the low level of public awareness, especially traders regarding Islamic banks, with the proven traders who still conduct transactions through conventional banks and even individuals (daily banks). Therefore, this study was conducted to determine whether or not there is a relationship between knowledge, religiosity, and social environment on the interest to save using Islamic banks. The method of this research is quantitative with an associative approach. The number of sample as 70 respondents with data collection methods using questionnaires and interview. Purposive sampling is a technique for sampling. The data analysis uses multiple correlation test, T test, F test, and coefficient of determination test (R2). The results of this research are that there is a positive and significant relationship between variables of knowledge and social environment on saving money interest using Islamic banks with tcount values of 2.014 and 2.913. While the religiosity variable does not have a significant relationship to the interest in saving money using an Islamic bank with a tcount of 0.655. The coefficient of determination test (R2) gets a result of 23%, it means that the variables of knowledge, religiosity, and social environment only have a role of 23% of interest in saving using Islamic banks and the rest is controlled by other variables that is not tested in this study.